The roots of religious extremism understanding the Salafi doctrine of Al-Wala' wal Bara' - Bin Ali, Mohamed (Imperial College Press insurgency and terrorism series, 2016)
One of the issues in contemporary Islamic thought which has attracted considerable attention amongst Muslim scholars and within the Muslim community is the valid and appropriate attitude of Muslims to relationships with non-Muslims. A major source of confusion and controversy with regards to this relationship comes from the allegation that Muslims must reserve their love and loyalty for fellow Muslims, and reject and declare war on the rest of humanity ? most acutely seen through the Islamic concept of Al-Wala' wal Bara' (WB) translated as "Loyalty and Disavowal", which appears to be central in the ideology of modern Salafism.This book investigates the dynamics and complexities of the concept of WB within modern Salafism and aims to understand the diverse interpretation of this concept; and how modern Salafis understand and apply the concept in contemporary religious, social and political settings. The book discovers that the complexities, diversities and disputes surrounding the concept in modern Salafism often revolve around issues of social, political and current realities.The significance of this book lies in the fact that comprehending modern Salafis' conception of WB, its realities and complexities has become an urgent priority in the lives of Muslims today